Reporte de reacciones adversas a medicamentos con compromiso mucocutáneo en Hospital Clínico Universidad de Chile durante los años 2004-2010 - Ramírez R., Constanza; Faúndez L., Eliana; Orellana B., Rodrigo (Revista Hospital Clínico Universidad de Chile, 2011)
Adverse drug reactions (ADRs) are responsible for up to 10% of hospital admissions worldwide; within them, that mucocutaneous reactions are the most common represented 30% of the total. The aim of this study was to analyze 119 reports of ADRs recorded in the Pharmacy Department of University of Chile Clinical Hospital in the period 2004-2010 by gender, age, most frequent clinical presentations, drugs and health personnel linked to the notification. In addition, we tried to quantify the relative importance of mucocutaneous reactions in the total of reported ADRs. ADRs were more common in women (56.3%). The average age was 52.84 years + / - 7.77, 52.07 + / - 10.6 for women and 53.84 + / - 13.43 for men without significant differences (p = 0.85). According to the clinical presentation, mucocutaneous reactions were the most frequent (31.1%) followed by hematological (25.2%). The drugs involved were chemotherapy (68.9%), antibiotics (5.9%) and NSAIDs, nonsteroidal anti-inflammatory drugs, (4.2%). In health personnel linked to the notification, we found the association medical / pharmaceutical chemist was the most frequent (40.3%), followed by a pharmaceutical chemist (33.6%). In mucocutaneous ADRs we observed a mean age of 54.65 + / - 9.19 years and female predominance (62.2%). According to the clinical dermatology, we observed a prevalence of skin rash (35.1%), mucositis (21.6%), facial erythema (16.2%) and pruritus (16.2%). The drugs involved were chemotherapy (78.4%), antibiotics (8%), antiretroviral therapy (5%) and opioids (5%). Finally, we found that according to time of onset, delayed reactions were the most frequent (43.2%).